Promoting students’ critical thinking skills through project-based learning in Indonesian higher education - Umam, Amalul; Fauziah, Zulfha Nurul; Rahmawati, Movie Riana; Jaelani, Alan (JEES (Journal of English Educators Society), 2022)
This research is focused on promoting students’ critical thinking skills through project-based learning. Thus, this study aims at (1) examining the idea of critical thinking, (2) discussing ways of improving critical thinking learners and (3) measuring learners' capacity of critical thinking using project-based learning approaches. This method of study is non-empirical by taking a qualitative approach to students' analytical thought and project-based learning perspectives. By incorporating this project-based learning, students can improve innovation and exercise criticism. By doing this study, we encourage other scholars to carry out research by means of project-based methods of learning. HIGHLIGHTS: Suspension of judgment is a situation when someone is rationally able to suspend their judgment in taking a conclusion about something. The suspension of judgments on subjects, objects, ideas, or whatever you wish to study is one of the most critical tasks. Open-mindedness is a virtue of intellectual nature with characteristic goals, including increasing or improving the cognitive interaction with reality. It involves specialized cognitive skills, including those involved in making information comprehensible to themselves and auxiliary habits, thus cognitive skills are truly engaged if necessary. Critical thinkers will motivate themselves to make solving the problem simpler for themselves.